2001
DOI: 10.1097/00004703-200102000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Language Outcomes of Children With History of Bronchopulmonary Dysplasia and Very Low Birth Weight

Abstract: A prospective follow-up of very low birth weight (VLBW) infants with and without bronchopulmonary dysplasia (BPD) and term control infants was conducted. The effects of BPD and VLBW on speech-language development and specific language impairment at 3 years of age were investigated, controlling for the effects of sociodemographic and other medical risk factors. Groups were compared on cognitive and speech-language outcomes using the Battelle Language and Bayley Mental Scales of Infant Development. Children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
3
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 39 publications
6
64
3
7
Order By: Relevance
“…Nine studies conducted in English-speaking populations [36][37][38][39][40][41][42][43][44] and 7 studies from non-English-speaking populations 45-51 met inclusion criteria ( Table 2). The most consistently reported risk factors include a family history of speech and language delay, male gender, and perinatal risk factors; however, their role in screening is unclear.…”
Section: Key Question 2a: Does Identification Of Risk Factors Improvementioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies conducted in English-speaking populations [36][37][38][39][40][41][42][43][44] and 7 studies from non-English-speaking populations 45-51 met inclusion criteria ( Table 2). The most consistently reported risk factors include a family history of speech and language delay, male gender, and perinatal risk factors; however, their role in screening is unclear.…”
Section: Key Question 2a: Does Identification Of Risk Factors Improvementioning
confidence: 99%
“…37,39,42 Three 37,41,43 of 5 studies reported an association between lower maternal education level and language delay, and 3 studies 41-43 of 4 that evaluated paternal education level reported a similar relationship. Other associated risk factors that were reported less consistently included childhood illnesses, 36,40 born late in the family birth order, 42 family size, 39 older parents 39 or younger mother 43 at birth, and low socioeconomic status (SES) or minority race. 40 One study that evaluated history of asthma found no association with speech and language delay.…”
Section: Key Question 2a: Does Identification Of Risk Factors Improvementioning
confidence: 99%
See 1 more Smart Citation
“…3 Apart from gestational age, several risk factors have been associated with poor development. These include abnormal cranial ultrasound scan, 4,5 bronchopulmonary dysplasia, 4,5 longer hospital stay, 6 multiplicity, 7 and male sex. [7][8][9] Children with poor growth also tend to have poorer developmental outcome.…”
mentioning
confidence: 99%
“…There are various longitudinal studies related to the developmental outcome of infants born prematurely 10,11,12 . The early intervention institute at Utah University reviewed 316 articles suggested that early intervention has immediate positive effect 13 .…”
Section: Introductionmentioning
confidence: 99%